Impact of pyrexia on neurochemistry and cerebral oxygenation after acute brain injury. Issue 8 (15th July 2005) - Stocchetti, N; Protti, A; Lattuada, M; Magnoni, S; Longhi, L; Ghisoni, L; Egidi, M; Zanier, E R
Abstract : Background: Postischaemic pyrexia exacerbates neuronal damage. Hyperthermia related cerebral changes have still not been well investigated in humans. Objective: To study how pyrexia affects neurochemistry and cerebral oxygenation after acute brain injury. Methods: 18 acutely brain injured patients were studied at the onset and resolution of febrile episodes (brain temperature ⩾38.7°C). Intracranial pressure (ICP), brain tissue oxygen tension (Pbr o 2 ), and brain tissue temperature (Tbr ) were recorded continuously; jugular venous blood was sampled intermittently. Microdialysis probes were inserted in the cerebral cortex and in subcutaneous tissue. Glucose, lactate, pyruvate, and glutamate were measured hourly. The lactate to pyruvate ratio was calculated. Results: Mean (SD) Tbr rose from 38 (0.5) to 39.3 (0.3)°C. Arteriojugular oxygen content difference (AJDo 2 ) fell from 4.2 (0.7) to 3.8 (0.5) vol% (p<0.05) and Pbr o 2 rose from 32 (21) to 37 (22) mm Hg (p<0.05). ICP increased slightly and no significant neurochemical alterations occurred. Opposite changes were recorded when brain temperature returned towards baseline. Conclusions: As long as substrate and oxygen delivery remain adequate, hyperthermia on its own does not seem to induce any further significant neurochemical alterations. Changes in cerebral blood volume may, however, affect intracranial pressure.